Pembuatan pabrik gula untuk meningkatkan kesejahteraan masyarakat Tlogowaru Malang - Helmy Mukti Himawan; Aditya Kurniawan; Imam Kusyairi; Rizki Priya P; Yuke Hary Laksono (Yumary: Jurnal Pengabdian kepada Masyarakat, 2020)
Purpose: This study aimed to increase partners' knowledge and skills regarding the use of various equipment for processing sugarcane into solid brown sugar so as to improve the economy of the farmers. Method: 5 steps were carried out in this activity; determining the location, determining a suitable place for the construction of a sugar factory, determining suitable business units, training on appropriate technology and brown sugar factory assembly and how to influence it & training on making units business ventures and marketing results, and sustainability evaluation of the program. Results: Processing raw sugarcane into brown sugar allows partners to directly improve their economic conditions by converting sugarcane into semi-finished products, namely brown sugar that is ready to sell to the industry, especially the soy sauce industry. Conclusion: The processing of raw sugarcane into brown sugar can directly improve its economic condition by converting sugarcane into semi-finished products. And there are several factors that inhibit or tighten the manufacture of brown sugar. Keywords: Sugar cane, Brown sugar, Yield